Zero tolerance policies in schools - Daniels, Peggy (Detroit : Greenhaven Press, 2009)
Looks at zero tolerance policies in U.S. public schools, authors debate the effectiveness and fairness of such policies.
Includes bibliographical references (p. 144-148) and index.
Keywords: School discipline -- United States; Classroom management -- United States